Siliceous spicules in marine demosponges (example Suberites domuncula) - Muller, W E G; Belikov, S I; Tremel, W; Perry, C C; Gieskes, W W C; Boreiko, A; Schroder, H C; Mueller, W E G; Schroeder, H C (Micron, 2006)
All metazoan animals comprise a body plan of different complexity. Since-especially based on molecular and cell biological data-it is well established that all metazoan phyla, including the Porifera (sponges), evolved from a common ancestor the search for common, basic principles of pattern formation (body plan) in all phyla began. Common to all metazoan body plans is the formation of at least one axis that runs from the apical to the basal region; examples for this type of organization are the Porifera and the Cnidaria (diploblastic animals). It seems conceivable that the basis for the formation of the Bauplan in sponges is the construction of their skeleton by spicules. In Demospongiae (we use the model species Suberites domuncula) and Hexactinellida, the spicules consist of silica. The formation of the spicules as the building blocks of the skeleton, starts with the expression of an enzyme which was termed silicatein. Spicule growth begins intracellularly around an axial filament composed of silicatein. When the first layer of silica is made, the spicules are extruded from the cells and completed extracellularly to reach their the final form and size. While the first steps Of spicule formation within the cells are becoming increasingly clear, it remains to be studied how the extracellularly present silicatein strings are formed. The understanding of especially this morphogenetic process will allow an insight into the construction of the amazingly diverse skeleton of the siliceous sponges animals which evolved between two periods of glaciations, the Sturtian glaciation (710-680 MYA) and the Varanger-Marinoan ice ages (605-585 MYA). Sponges are-as living fossils-witnesses of evolutionary trends which remained unique in the metazoan kingdom. (c) 2005 Elsevier Ltd. All rights reserved.